Design of Pineapple Peeler with Manual Press System - Iin Sawitri; Ainun Rohana; Sulastri Panggabean (Jurnal Rekayasa Pangan dan Pertanian, 2014)
Basicly, oil press is designed to press  candlenut. This study was used in testing various commodity on oil press which was aimed to find the capacity of the oil press in removing oil from grains besides candlenut. This study was conducted at the Laboratory of Agricultural Engineering and parameters were analysed at Laboratory of Food Technology Faculty of Agricultural USU in March to May 2014 by using a non factorial completly randomized on peanut, soybean and corn. Parameters measured were effective capacity of oil press, water content of oil and yield. The results showed that the commodities had highly significant effect on effective capacity, water content and yield. The best treatment was the P1 (peanut) which produced 1,536 l/kg effective capacity, 0,171% water content of oil and 0,367 l/kg yield. Keywords: Grains oil, oil press, pressing